ORGANISASI DAN LINGKUNGANNYA - Soliha, Euis; Maharani, Kurnia (Universitas Muhammadiyah Surakarta, 2011)
In this time every organizations challenge ever greater in developing its capacities. Organizations will do not want to deal with environment which always change. Only organizations Â fit with the environment, they will survive. The way of to increase power with acquition resources and copying uncertainty